1998
DOI: 10.1128/aem.64.4.1385-1389.1998
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between Bacillus thuringiensis Spores and Toxins against Resistant and Susceptible Diamondback Moths ( Plutella xylostella )

Abstract: We studied the effects of combinations of Bacillus thuringiensis spores and toxins on the mortality of diamondback moth (Plutella xylostella) larvae in leaf residue bioassays. Spores of B. thuringiensis subsp.kurstaki increased the toxicity of crystals of B. thuringiensis subsp. kurstaki to both resistant and susceptible larvae. For B. thuringiensis subsp.kurstaki, resistance ratios were 1,200 for a spore-crystal mixture and 56,000 for crystals without spores. Treatment of a spore-crystal formulation of B. thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…An obligate association with the gut microbiota challenges previous models of the pathogenicity of Bt toxins, and has considerable implications for the ecology of Bt and the evolution of novel resistance mechanisms in invertebrate pests. The gut microbiota hypothesis remains highly controversial, given previous evidence of the lethality Bt in aseptically reared insects (Takatsuka and Kunimi, 2000) and the synergistic action of the Bt spore on the toxicity of crystal toxins in some hosts (Heimpel and Angus, 1959; Li et al ., 1987; Liu et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…An obligate association with the gut microbiota challenges previous models of the pathogenicity of Bt toxins, and has considerable implications for the ecology of Bt and the evolution of novel resistance mechanisms in invertebrate pests. The gut microbiota hypothesis remains highly controversial, given previous evidence of the lethality Bt in aseptically reared insects (Takatsuka and Kunimi, 2000) and the synergistic action of the Bt spore on the toxicity of crystal toxins in some hosts (Heimpel and Angus, 1959; Li et al ., 1987; Liu et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…kurstaki, but not with Bt subsp. aizawai (Liu et al, 1998). Helicoverpa armigera (Hübner) larvae feeding on a diet with the same antibiotic cocktail as reported by Broderick et al (2006Broderick et al ( , 2010 did not develop resistance to Cry1Ab or Cry1Ac after transgenerational Bt exposure, but mortality was reduced 30% in the F3 generation of insects reared on antibiotics-free diet and exposed to Bt (Paramasiva et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…To pyramid transgenes in such clonal crops therefore requires either simultaneous transformation or retransformation approaches. It is important first to investigate how the expression of two dissimilar cry genes might interact in transgenic plants because Bt toxins can interact, with antagonistic (Lee et al , 1996; Del Rincón‐Castro et al , 1999), additive (Poncet et al , 1995) and synergistic (Tabashnik, 1992; Poncet et al , 1995; Lee et al , 1996; Liu et al , 1998) effects.…”
Section: Discussionmentioning
confidence: 99%
“…Such interaction studies have shown the synergistic effects of the Bt toxins on certain pests (e.g. Tabashnik, 1992; Poncet et al , 1995; Lee et al , 1996; Liu et al , 1998). However, the majority of such studies have been based on the use of either partially or wholly purified crystal proteins and spores of Bt .…”
Section: Introductionmentioning
confidence: 99%